Cognitive representations of handball tactic actions in athletes - The function of expertise and age - Vogel, L.; Schack, T. (PLOS ONE, 2023)
The tactical cooperation for the optimal interaction of team members is an essential performance-determining variable in sports games. The underlying cognitive memory structures of cooperative tactical actions have so far been little researched. Therefore, this study investigated the cognitive memory structure of tactical knowledge of handball actions in teams of different expertise and age groups. In the first experiment, tactical mental representation structures (TMRS) of 30 adult handball players of two different level of expertise were investigated. In the second experiment, TMRS of 57 youth handball players from three age levels were investigated. In both experiments the TMRS was measured with the structure dimensional analysis of mental representation (SDA-M) method. The SDA-M commences with a splitting procedure of a given set of concepts and reveals with a cluster analysis the relational structures of the concepts on an individual and a group level. Experiment one revealed that the TMRS differed significantly between skilled either/or less experienced handball players. Skilled handball players showed a hierarchical organized representation that shared more features with the basic tactical structure of the handball game than less experienced players. The second experiment revealed age-related differences of the TMRS between the age groups of the U15, U17 and U19 teams. Further data analysis revealed significant differences of the TMRS between experienced and less experienced handball players and between local and regional competition level players. We conclude that our current findings suggest that tactical expertise is mediated by elaborate cognitive tactical knowledge in memory. Furthermore, our results indicate that tactical knowledge plays a substantial role during tactical skill learning as it differs as function of age, experience, and competition level. From this point of view, team representations of game situations can be seen as a crucial factor for efficient and common interaction in fast-paced team sports.